Optimization of Gas-Water Absorption Equilibrium of Carbon Dioxide for Algae Liquors: Selection of Alkaline Buffering Chemicals - Wen-Hsi Cheng; Ming-Shean Chou (International Journal of Photoenergy)
The apparent Henry’s Law constant (H′), which quantifies the concentration partition of a gas-liquid equilibrium of carbon dioxide (CO2), is used to optimize the absorption of carbon dioxide in algae liquors. The values of H′ were examined under various conditions: in water at different temperatures (27 and 37°C), in alkaline buffering chemicals (sodium hydroxide (NaOH) and sodium carbonate (Na2CO3)), and in aquatic algae plants (Egeria densa and Anubias barteri nana). The optimal conditions for CO2 absorption can be obtained by controlling the aqueous pH values (around weak alkalinity with pH 9-10) using sodium carbonate as an alkaline buffering chemical at 27°C, yielding exact H′ values of around 16.3–21.3 atm/M, which were obtained from the mean gaseous CO2 concentration of 803 ppm and the total aqueous carbonate concentration of 4.085 mg/L. The experimental results reveal that an alkaline buffering compound, sodium carbonate, can be added to water to maintain a constant aqueous alkalinity enough for the fixation of carbon dioxide by the photosynthesis of green algae in a photobioreactor.